دراسة خطر فيضان وادي مزي على مدينة الاغواط. نظم المعلومات الجغرافية و الاستشعار عن بعد كاداة لدعم التخطيط الحضري والحماية من الكوارث الطبيعية. - ساعد سعود وحيد (Journal of Architecture and environment of child, 2020)
: The valleys’ floods constitution one of the patterns of environmental crises in the present time, due to the encroachment of urban and residential communities on their hydrological systems; This is in the absence of systematic planning based on clear rules, legal foundations, and applied mechanisms. Laghouat is a fragile desert environment model, in which urban features are well known. It was many times vulnerable to natural hazards like valleys’ flood, including the valley of M’zi and the auxiliary valley. The extension of the occupied geographical area and the non-control of the valleys’ elevations ring the alarm to urban as well as human beings. The use of geographic information system and remote sensing techniques, the exploitation of available satellite images and visuals, the computer software processing, and support for this in the field investigation enabled us to extract hydrological networks and leads to link them to urban growth and urban plans, whether current or forward-looking and our attempt to explain natural phenomena and proposals to reduce their risks. The results confirmed that most of the decisions of the current urban and structural plans in this environment are not directed and need a scientific evaluation based on scientific studies supported by technology, analysis, and reliable result.